Longitudinal associations between formal volunteering and well-being among retired older people: follow-up results from a randomized controlled trial - Jongenelis, Michelle; Jackson, B.; Newton, R.U.; Pettigrew, Simone (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
Volunteering has been identified as a potential mechanism for improving the psychosocial health of older adults. Utilizing a randomized controlled trial approach, the present study assessed the extent to which commencing volunteering can improve psychosocial health outcomes for older people. Fully retired Australian adults aged 60+ years (N= 445) were assessed at baseline and allocated to either the intervention or control arms of the trial. Those in the intervention condition were asked to participate in at least 60 min of formal volunteering per week for 6 months. Per-protocol analyses were conducted comparing psychosocial outcomes for those who complied with the intervention condition (n= 73) to outcomes for those who complied with the control condition (n= 112). Those who complied with the intervention condition demonstrated significant improvements in life satisfaction, purpose in life, and personal growth scores over a 12-month period relative to those in the control condition who did no volunteering. Findings provide evidence of a causal relationship between commencing volunteering and improvements in psychosocial health among older adults and indicate that encouraging participation in this activity could constitute an effective healthy aging intervention.